EFFECTIVENESS OF THE WORLD TRADE ORGANIZATION’S DISPUTE SETTLEMENT MECHANISM - Abdurrahman Alfaqiih (Fakultas Hukum Universitas Gadjah Mada, 2013)
Many WTO (World Trade Organization) member States have made use of the WTO dispute settlement mechanism. Nevertheless, the debate over the effectiveness of this mechanism is still happening and is animportant issue to be discussed. This article aims to explain the effectiveness of the WTO dispute settlement mechanism. Its time frame, participation (particularly developing countries) and its achievements areu sed to measure such effectiveness. This article concludes that the WTO dispute settlement mechanism effectively resolves the disputes among the members. Tidak sedikit negara-negara anggota WTO (World Trade Organization) memanfaatkan mekanisme penyelesaian sengketa dagang internasional di WTO. Namun demikian, perdebatan tentang keefektifan mekanisme ini masih terus terjadi dan menjadi isu yang penting untuk dikaji. Tulisan ini bertujuan untukmenjelaskan argumentasi efektifitas mekanisme penyelesaian sengketa dagang internasional di WTO. Pendekatan waktu, partisipasi (khususnya negara berkembang) dan pencapaian menjadi tolak ukur pengukuran efektifitas mekanisme tersebut. Tulisan ini menyimpulkan bahwa mekanisme penyelesaian sengketa dagang internasional di WTO berjalan secara efektif.